THE EFFECT OF CLOSED-LOOP COMMUNICATION ON REDUCING EMERGENCY ERRORS - Dedy Sambahtrah; Yosafat Barus (Getsempena Health Science Journal, 2026)
Emergency services are a high-risk area for errors due to time pressure, high workloads, and case complexity that require effective team coordination. One of the main factors contributing to errors in emergency procedures is communication failure among healthcare workers. Closed-loop communication is a structured communication method that emphasizes clear message delivery, repetition by the recipient, and reconfirmation by the person giving the order to ensure the message is understood correctly. This study aims to analyze the effect of closed-loop communication on reducing errors in emergency procedures in the Emergency Department of Bina Kasih General Hospital, Medan. This study used an observational analytical design with a cross-sectional approach. The study was conducted in September 2025 with 20 healthcare workers directly involved in emergency services. Sampling was carried out using a total sampling technique. Data were collected through observation sheets and structured questionnaires, then analyzed univariately and bivariately using the Chi-Square test. The results showed that respondents with good implementation of closed-loop communication experienced a lower level of errors compared to respondents with poor implementation of closed-loop communication. The statistical test results showed a p-value of 0.012, indicating a significant effect between the implementation of closed-loop communication and the reduction in emergency procedure errors. This study concluded that the implementation of closed-loop communication plays a significant role in improving patient safety and reducing the risk of procedure errors in emergency services.